Analyzing the Floating Market System in Thailand for Sustainability - Ichikawa, Takanori; Denpaiboon, Chaweewan (Journal of Architectural/Planning Research and Studies (JARS), 2017)
Humans and water share a close relationship in Thailand. Before modernization, Thailand had many canals, a developed water traffic system, and many floating markets. These markets functioned as community spaces for the inhabitants. Moreover, environmental sustainability had been reached and the system seemed important to the culture. In this work, the remaining floating markets in and around Bangkok are surveyed and then compared. The results are as follows. Bangkok has 28 floating markets, as of 2016. These markets can be divided into three types based on their “target customers.” Some markets used a temple site because temples function as community spaces for the local inhabitants; others are only meant for sightseeing and do not function as community spaces. Based on their contribution to the “local economy,” these markets can be divided into three types. The type of market differed according to location. The markets where anything is sold, however, are not useful to the local economy. The floating markets can be divided into four types based on their “space composition.” These markets are cool spaces, a characteristic of water spaces. Based on their “waterway network,” these markets can be divided into three types. Markets at closed sites are not connected to other places because they are only meant for tourists. Consequently, “target customers,” “local economy,” “space composition,” and “waterway network” are determined as necessary factors in considering a sustainable floating market system in the present and future. This study contributes to adopting a sustainable development concept of a floating market in attracting policymakers and local people to draw tourist appeal.